Current issues in immunisation: Diphtheria in Australia, recent trends and future prevention strategies - Gidding, Heather F; Burgess, Margaret A; Gilbert, Gwendolyn L (Communicable Diseases Intelligence, 2000)
Diphtheria has become rare in Australia. This article focuses on the recent epidemiology of diphtheria and ways of preventing its recurrence in Australia.